The state of agricultural extension services in Sri Lanka, 2024-2025 - van Asselt, Joanna; Weerasinghe, Krishani; Hemachandra, Delini; Jayaweera, Anuradha; Munasinghe, Dilusha; Headey, Derek D. (International Food Policy Research Institute, 2025)
We assess the state of Sri Lanka’s agricultural extension services using the BRIGHT 2024-2025 national survey. We examine use of or access to extension by land size and wealth, farmers’ trust in different providers, and farmers use of innovative sources of extension, including digital channels.. • Fifty-five percent of Sri Lankan farmers accessed some form of extension in 2024/2025 • Public extension agents remain the most trusted source of advice, yet their reach differs sharply by region—from as high as 75% in North-Western Province to as low as 30% in Northern Province. • Access to agricultural extension varies widely across provinces, with the highest access in Northern Province (84%) and the lowest in Central and Western Provinces (around 44%). • In the Northern Province, despite low public provision, farmers compensate through strong reliance on input retailers (64%) and Farmers’ Organizations (71%), indicating robust informal ex-tension networks. • Extension access is strongly related to cultivated area and asset ownership. Only 40% of farmers cultivating less than 0.5 acres received any form of extension, compared to 71% among those with more than 3 acres. Similarly, only 39% of households in the lowest wealth quintile accessed extension, compared to 62% in the highest quintile. • Wealthier farmers and those with more cultivated acres not only access extension more frequently but also from a wider range of sources, underscoring inequality in information access and opportunity. • Digital channels, such as Facebook and other online groups, play a growing but still limited role, concentrated mainly in the Western Province where internet access is strongest.